Synchrotron quantification of ultrasound cavitation and bubble dynamics in Al–10Cu melts - Xu, WW; Tzanakis, I; Srirangam, P; Mirihanage, WU; Eskin, DG; Bodey, AJ; Lee, PD (Elsevier, 2016)
Knowledge of the kinetics of gas bubble formation and evolution under cavitation conditions in molten alloys is important for the control casting defects such as porosity and dissolved hydrogen. Using in situ synchrotron X-ray radiography, we studied the dynamic behaviour of ultrasonic cavitation gas bubbles in a molten Al–10 wt% Cu alloy. The size distribution, average radius and growth rate of cavitation gas bubbles were quantified under an acoustic intensity of 800 W/cm2 and a maximum acoustic pressure of 4.5 MPa (45 atm). Bubbles exhibited a log-normal size distribution with an average radius of 15.3 ± 0.5 μm. Under applied sonication conditions the growth rate of bubble radius, R(t), followed a power law with a form of R(t) = αtβ, and α = 0.0021 & β = 0.89. The observed tendencies were discussed in relation to bubble growth mechanisms of Al alloy melts.